Strategi Komunikasi PT Semen Indonesia (PERSERO) Tbk Dalam Manajemen Isu Pembangunan Pabrik Semen Di Rembang - Sigit Wahono (Program Studi Ilmu Komunikasi FISIP UM Buton, 2020)
This study aims to identify, analyze, and determine the factors that influence the success of the communication strategy undertaken by PT Semen Indonesia (Persero)Tbk in the issue management of the cement plant construction in Rembang used descriptive qualitative research methods with case studies. Based on the results of the research, Semen Indonesia has made efforts to actively manage the issue by conducting media monitoring every day to monitor the development of news and information circulating in the print and online mass media. Issue monitoring is also carried out by observing public opinion on social media and various other online discussion forums. Furthermore, Semen Indonesia has compiled a communication strategy in managing the issue of cement factory construction in Rembang which is divided into several elements, including messages delivered, mapping of communication targets, communication media used, and evaluating the impacts obtained from the communication strategies that have been carried out. The communication strategy has been implemented in accordance with the planned schedule. In carrying out the management of the issue, Semen Indonesia carried out the appropriate information between the data and the available facts. To reach all broader stakeholders, Semen Indonesia uses a variety of existing communication media. The company also conducts periodic evaluations to determine the effectiveness of the communication strategy undertaken. In addition to monitoring issues based on mass media and social media, strategy adjustments are made by analyzing the development of actions and agenda settings carried out by counter parties.